2019
DOI: 10.5658/wood.2019.47.3.324
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Mechanical Properties of Methyl Methacrylate-Impregnated Wood from Three Fast-Growing Tropical Tree Species

Abstract: Timber from plantation forests has inferior physical and mechanical properties compared to timber from natural forest because it is mostly from fast-growing tree species that are cut at a young age. Filling cell voids with methyl methacrylate (MMA) can improve the wood properties. The purpose of this study was to determine the physical and mechanical properties of MMA-impregnated wood from three fast-growing wood species, namely jabon (Anthocephalus cadamba (Roxb.) Miq.), mangium (Acacia mangium Willd) and pin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 15 publications
0
14
0
1
Order By: Relevance
“…The introduction of monomers and the subsequent in situ polymerization of these monomers into a polymer chain is one approach to permanently encapsulating novel materials in wood. These compounds undergo in situ polymerization after being exposed to radiation (Hadi et al 2019) or by radical initiator at elevated temperatures (Che et al 2018). A wide variety of vinyl monomers that are commercially available on the market, including acrylonitrile, glycidyl methacrylate, methyl methacrylate, hydroxyethylene, ethylene glycol, dimethacrylate, butyl acrylate, butyl methacrylate, styrene, acrylamide, or acrylonitrile, have been studied by several researchers.…”
Section: Nonbonded Leachable (Nbl)mentioning
confidence: 99%
See 1 more Smart Citation
“…The introduction of monomers and the subsequent in situ polymerization of these monomers into a polymer chain is one approach to permanently encapsulating novel materials in wood. These compounds undergo in situ polymerization after being exposed to radiation (Hadi et al 2019) or by radical initiator at elevated temperatures (Che et al 2018). A wide variety of vinyl monomers that are commercially available on the market, including acrylonitrile, glycidyl methacrylate, methyl methacrylate, hydroxyethylene, ethylene glycol, dimethacrylate, butyl acrylate, butyl methacrylate, styrene, acrylamide, or acrylonitrile, have been studied by several researchers.…”
Section: Nonbonded Leachable (Nbl)mentioning
confidence: 99%
“…After 24 h soaking, WA may be lowered from 50% (untreated) to ≈ 20%. Hadi et al (2019) investigated the effects of methyl methacrylate (MMA) impregnation on different wood species. They observed that the WPG of MMA-treated wood was around 14.62 to 23.75%; hence, it could achieve a WA of around 24% to 56.7%.…”
Section: Nonbonded Leachable (Nbl)mentioning
confidence: 99%
“…Fast-growing wood species dominate the production of this log. Fast-growing trees are a particular kind of woody plant with a harvest time of fewer than 10 years [2][3][4][5][6][7] This kind of plant is widely grown in Industrial Plantation Forests (HTI) and Community Plantation Forests (HTR) due to its quick harvesting phase [5]. However, the standard essential features this fast-growing plant species has, such as its low-density value and low level of dimensional stability, provide issues in its application [8].…”
Section: Introductionmentioning
confidence: 99%
“…Antonios N. et al [9] chemically modified wood by acetic anhydride and found that acetylation significantly affected the toughness of wood. Hadi Y. S. et al [10] impregnated wood by methyl methacrylate (MMA) and heated it to induce the polymerization process and found that the wood impregnated by MMA was physically and mechanical properties were improved. SH Lee et al [11] believed that, after oil heat treatment, the equilibrium moisture content of wood decreases, the compressive strength along the grain increases, and the change of mechanical properties brings strong moisture resistance, dimensional stability, and biological durability, which can be applied to floors and outdoor buildings.…”
Section: Introductionmentioning
confidence: 99%